THE EFFORTS TO INCREASE THE USE VALUE OF CORN THROUGH EMPING CHIPS PROCESSING IN SIOPAT SOSOR VILLAGE, PANGURURAN SUB-DISTRICT, SAMOSIR DISTRICT - Sutanti, Siti; Mutiara, Erli; Dalimunthe, Dian Agustina (Journal of Community Research and Service, 2020)
Corn is an agricultural commodity that is widely grown by farmers. The abundant corn harvest during the main season has caused the selling price of corn to decline. These conditions prompted the Community Service team to implement the PKM program for processing corn emping chips for partners. The partners of this activity are 1) Mekar Jaya Farmers and Nainggolan Farmers are located in Siopat Sosor Village, Pangururan Sub-District, Samosir District. The objectives of this activity are 1) Designing a corn emping chips machine; 2) to improve product quality partners need to make more attractive packaging; 3) Assistance in production and marketing processes. This PKM activity begins with providing knowledge, technology and business management as well as online marketing. Corn farmers can take advantage of their agricultural products by processing corn emping chips. Corn emping chips are made from boiled corn which is flaked using a corn flakes machine with a capacity of 50 kg / hour, then dried in the sun and when it's dry it is ready to be fried and then enjoyed. Corn emping chips are one of the most valuable corn processed products. Corn emping chips are a food diversification product that can support the development of rural agro-industries and can increase the income of corn farmer families.